Manufacturing and economic development - Adam Szirmai (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
This paper examines the theoretical and empirical evidence for the hypothesis that manufacturing is the main engine of growth in developing countries. The paper opens with an overview of the main arguments supporting the engine of growth hypothesis and then examines each of these arguments using a mix of statistical analysis of secondary data and secondary literature. The paper concludes that manufacturing will continue to be important in accelerating growth and achieving catch-up in developing countries. However, compared to the past 60 years, market service sectors will become relatively more important as potential sources of growth and catch up.
Keywords: O14; N6; 330; structural change; manufacturing; engine of growth; catch-up